Distinct interaction between management history and nitrogen source drive microbial nitrogen processes in soil - Misato Toda; Michael Scheifele; Jochen Mayer; Marcel G.A. van der Heijden; Florian Walder (Applied Soil Ecology, 2026)

Drought increases root and rhizodeposition carbon inputs into soils - Elena Kost; Dominika Kundel; Matti Barthel; Rafaela Feola Conz; Roland Anton Werner; Shiva Ghiasi; Tabata Aline Bublitz; Paul Mäder; Hans-Martin Krause; Johan Six; Martin Hartmann; Jochen Mayer (Plant and Soil, 2026)
Aims Increasing droughts affect crop yield and health. Plants can respond to drought by adapting their root biomass, root morphology, and quality and quantity of rhizodeposition to improve water and nutrient uptake. Besides droughts, agricultural management influences roots and rhizodeposition; however, it is not well studied how agricultural management can affect the response of roots and rhizodeposition to drought. Methods A semi-continuous 13 CO 2 isotope labelling experiment was performed in a long-term field experiment comparing biodynamic, mixed conventional, and mineral conventional cropping systems. Rainout shelters were installed to induce drought. Root, net rhizodeposition, and the rhizosphere microbiome were determined at ripening of wheat. Results Drought enhanced the total root carbon mainly through the increase of fine roots. Fine root carbon under drought was primarily enhanced in the mixed conventional and biodynamic cropping system, both receiving farmyard manure, whereas no increase was measured in the mineral fertilized conventional system. Net rhizodeposition carbon was enhanced in all cropping systems under drought, particularly in the first 0.25 m. While some plant-growth-promoting genera such as Streptomyces and Rhizophagus showed relative increases under drought, other plant growth-promoting genera often involved in nitrogen fixation such as Rhodoferax and Mesorhizobium were decreased. Conclusion This field trial suggests that drought increases total belowground carbon input via fine root and net rhizodeposition carbon inputs. Since fine root carbon increased under drought in cropping systems with farmyard manure, adding manure under future drought periods could be advantageous to increase soil carbon inputs and improve nutrient foraging.

Exploring the impact of siloxane networks on the thermal behavior of P/N-enriched flame-retardant finishes for cotton fabric - Raphael Otto; Wael Ali; Eui-young Shin; Alexander M. Preußner; Hung M. Phan; Torsten Textor; Jochen S. Gutmann; Thomas Mayer-Gall (Chemical Engineering Journal, 2025)

Soil extracellular polymeric substances and microbial biomass react differently to field induced drought stress in contrasting cropping systems at different wheat developmental stages - Tabata Aline Bublitz; Elena Kost; Dominika Kundel; Oluwaseun ldowu Alimi; Anke Hupe; Paul Mäder; Hans-Martin Krause; Jochen Mayer; Martin Hartmann; Rainer Georg Joergensen (Biology and Fertility of Soils, 2025)
Drought events are becoming more severe and recurrent over Europe. Changes in temperature and rain patterns can affect soil nutrient mobility and availability, modulating the biomass and activity of soil microbial communities. Here, we investigated the effects of drought on extracellular polymeric substances (EPS) and microbial biomass carbon (MBC) and nitrogen (MBN) in differently managed cropping systems. An on-field drought simulation experiment using rain-out shelters was conducted as part of a long-term field experiment cultivated with winter wheat, comparing cropping systems with contrasting fertilization strategies and crop protection measures: A biodynamic system and a mixed conventional system with no pesticide application, and a purely minerally fertilized conventional system, with conventional pesticide use. The implemented drought lasted for three months, starting at plant tillering stage and ending at ripening stage. No watering was performed on the drought treatment during that period. Soils were sampled at stem elongation, flowering, and ripening. EPS-carbohydrates and EPS-proteins significantly increased by approximately 20% due to induced drought but remained roughly constant from stem elongation to ripening under drought. Mean EPS-carbohydrates to EPS-proteins ratio was 1.9. MBC and MBN remained largely unaffected by drought. The ratio of both EPS fractions to microbial biomass was lowest in the biodynamic system and highest in the minerally fertilized conventional system, indicating that rhizodeposits and mucilage were predominantly diverted into microbial biomass, rather than into microbial EPS. This might be an important reason for the higher soil fertility of the biodynamic system.

Organic cropping systems alter metabolic potential and carbon, nitrogen and phosphorus cycling capacity of soil microbial communities - Hans-Martin Krause; Ralf C. Mueller; Martina Lori; Jochen Mayer; Paul Mäder; Martin Hartmann (Soil Biology and Biochemistry, 2025)

Cropping system modulates the effect of spring drought on ammonia-oxidizing communities - Ari Fina Bintarti; Elena Kost; Dominika Kundel; Rafaela Feola Conz; Paul Mäder; Hans-Martin Krause; Jochen Mayer; Laurent Philippot; Martin Hartmann (Soil Biology and Biochemistry, 2025)

Soil microbial resistance and resilience to drought under organic and conventional farming - Elena Kost; Dominika Kundel; Rafaela Feola Conz; Paul Mäder; Hans-Martin Krause; Johan Six; Jochen Mayer; Martin Hartmann (European Journal of Soil Biology, 2024)

Nitrogen-15 natural abundance is robust to quantify nitrogen transfer from clover to grass in temporary grassland - Andreas Hammelehle; Jochen Mayer; Andreas Lüscher; Astrid Oberson (Soil Biology and Biochemistry, 2024)

Soil aggregate stability governs field greenhouse gas fluxes in agricultural soils - Stijn G. van den Bergh; Iris Chardon; Márcio F.A. Leite; Gerard W. Korthals; Jochen Mayer; Mathias Cougnon; Dirk Reheul; Wietse de Boer; Paul L.E. Bodelier (Soil Biology and Biochemistry, 2024)

Organic cropping systems maintain yields but have lower yield levels and yield stability than conventional systems – Results from the DOK trial in Switzerland - Samuel Knapp; Lucie Gunst; Paul Mäder; Shiva Ghiasi; Jochen Mayer (Field Crops Research, 2023)

Emissions of nitrous oxide and methane after field application of liquid organic fertilizers and biochar - Norah Efosa; Hans-Martin Krause; Roman Hüppi; Maike Krauss; Nadège Vaucher; Flora Zourek; Jochen Mayer; Johan Six; Else K. Bünemann (Agriculture, Ecosystems & Environment, 2023)

Modelling phosphorus dynamics in four European long-term experiments - Anna Muntwyler; Panos Panagos; Francesco Morari; Antonio Berti; Klaus A. Jarosch; Jochen Mayer; Emanuele Lugato (Agricultural Systems, 2023)

Long-term differences in fertilisation type change the bacteria:archaea:fungi ratios and reveal a heterogeneous response of the soil microbial ionome in a Haplic Luvisol - Sanja A. Schwalb; Shiwei Li; Michael Hemkemeyer; Stefanie Heinze; Rainer Georg Joergensen; Jochen Mayer; Paul Mäder; Florian Wichern (Soil Biology and Biochemistry, 2023)

Geospatial Information Research: State of the Art, Case Studies and Future Perspectives - Ralf Bill; Jörg Blankenbach; Martin Breunig; Jan-Henrik Haunert; Christian Heipke; Stefan Herle; Hans-Gerd Maas; Helmut Mayer; Liqui Meng; Franz Rottensteiner; Jochen Schiewe; Monika Sester; et al. (PFG – Journal of Photogrammetry, Remote Sensing and Geoinformation Science, 2022)
Geospatial information science (GI science) is concerned with the development and application of geodetic and information science methods for modeling, acquiring, sharing, managing, exploring, analyzing, synthesizing, visualizing, and evaluating data on spatio-temporal phenomena related to the Earth. As an interdisciplinary scientific discipline, it focuses on developing and adapting information technologies to understand processes on the Earth and human-place interactions, to detect and predict trends and patterns in the observed data, and to support decision making. The authors – members of DGK, the Geoinformatics division, as part of the Committee on Geodesy of the Bavarian Academy of Sciences and Humanities, representing geodetic research and university teaching in Germany – have prepared this paper as a means to point out future research questions and directions in geospatial information science. For the different facets of geospatial information science, the state of art is presented and underlined with mostly own case studies. The paper thus illustrates which contributions the German GI community makes and which research perspectives arise in geospatial information science. The paper further demonstrates that GI science, with its expertise in data acquisition and interpretation, information modeling and management, integration, decision support, visualization, and dissemination, can help solve many of the grand challenges facing society today and in the future.

Preface to the thematic issue on mineral systems of West Africa - Nicolas Thébaud; Aurélien Eglinger; Anne-Sylvie André-Mayer; Jochen Kolb (Mineralium Deposita, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Visiting dark sides of model simulation of carbon stocks in European temperate agricultural soils: allometric function and model initialization - Arezoo Taghizadeh-Toosi; Wen-Feng Cong; Jørgen Eriksen; Jochen Mayer; Jørgen E. Olesen; Sonja G. Keel; Margaret Glendining; Thomas Kätterer; Bent T. Christensen (Plant and Soil, 2020)

A comprehensive and comparative phenotypic analysis of the collaborative founder strains identifies new and known phenotypes - Heike Kollmus; Helmut Fuchs; Christoph Lengger; Hamed Haselimashhadi; Molly A. Bogue; Manuela A. Östereicher; Marion Horsch; Thure Adler; Juan Antonio Aguilar-Pimentel; Oana Veronica Amarie; Lore Becker; Johannes Beckers; et al. (Mammalian Genome, 2020)
The collaborative cross (CC) is a large panel of mouse-inbred lines derived from eight founder strains (NOD/ShiLtJ, NZO/HILtJ, A/J, C57BL/6J, 129S1/SvImJ, CAST/EiJ, PWK/PhJ, and WSB/EiJ). Here, we performed a comprehensive and comparative phenotyping screening to identify phenotypic differences and similarities between the eight founder strains. In total, more than 300 parameters including allergy, behavior, cardiovascular, clinical blood chemistry, dysmorphology, bone and cartilage, energy metabolism, eye and vision, immunology, lung function, neurology, nociception, and pathology were analyzed; in most traits from sixteen females and sixteen males. We identified over 270 parameters that were significantly different between strains. This study highlights the value of the founder and CC strains for phenotype-genotype associations of many genetic traits that are highly relevant to human diseases. All data described here are publicly available from the mouse phenome database for analyses and downloads.

Above- and belowground nitrogen distribution of a red clover-perennial ryegrass sward along a soil nutrient availability gradient established by organic and conventional cropping systems - Andreas Hammelehle; Astrid Oberson; Andreas Lüscher; Paul Mäder; Jochen Mayer (Plant and Soil, 2018)

Coherent response of a group of plantation-grown Scots pine trees to wind loading - Dirk Schindler; Hannes Fugmann; Jochen Schönborn; Helmut Mayer (European Journal of Forest Research, 2012)

Evaluation of the wick method for in situ 13C and 15N labelling of annual plants using sugar-urea mixtures - Florian Wichern; Jochen Mayer; Rainer Joergensen; Torsten Müller (Plant and Soil, 2010)

Association of angiotensin-converting enzyme 2 (ACE2) gene polymorphisms with parameters of left ventricular hypertrophy in men - Wolfgang Lieb; Jochen Graf; Anika Götz; Inke R. König; Björn Mayer; Marcus Fischer; Jan Stritzke; Christian Hengstenberg; Stephan R. Holmer; Angela Döring; Hannelore Löwel; Heribert Schunkert; et al. (Journal of Molecular Medicine, 2006)

Turnover of grain legume N rhizodeposits and effect of rhizodeposition on the turnover of crop residues - Jochen Mayer; Michael Schloter; Jrgen He; Franz Buegger; Erik Steen Jensen (Biology and Fertility of Soils, 2004)

Residual nitrogen contribution from grain legumes to succeeding wheat and rape and related microbial process - Jochen Mayer; Franz Buegger; Erik Steen Jensen; Michael Schloter; Jürgen Heß (Plant and Soil, 2003)